Ultrasound in photoelectrochemistry: a new approach to the enhancement of the efficiency of semiconductor electrode processes. - Compton, R; Akkermans, R; Coles, B; Marken, F (1997)
A novel photoelectrochemical experiment which simultaneously allows the illumination of a TiO2 semiconductor electrode surface and the application of power ultrasound emission is described. The horn probe of an immersion horn transducer is modified by an oxide coated titanium tip and placed in a conventional three electrode electrochemical cell which allows light from a monochromated source to be focussed onto the electrode surface. Well-defined photocurrents are observed in aqueous media and for the photoinduced oxidation of water in acetonitrile and of 2.4-dichlorophenol in acetonitrile. The effect of ultrasound is to shift the observed photocurrent responses to more negative potentials and therefore to enhance the observed processes. Several possible interpretations associated with the complex effects induced by ultrasound are considered and a model based mainly on the extreme change of mass transport at the semiconductor/solution interface is suggested. Considerably enhanced performance for non-Nernstian processes, such as those observed in photoelectrochemical reactions at semiconductor electrodes, can be achieved in the presence of ultrasound.